Reniuristis brevicoxus gen. et sp. nov. (Amphipoda, Lysianassoidea, Uristidae) described from Site F cold seep in the South China Sea - Wang, Yan-Rong; Sha, Zhong-Li (Zootaxa, 2026)
The biodiversity of Site F, a cold seep in the South China Sea, still has some knowledge gaps. Reniuristis brevicoxus gen. et sp. nov. is the first epibenthic amphipod reported at Site F. The new genus Reniuristis gen. nov. differs from other genera of the family Uristidae Hurley, 1963 by the combination of the following characters: a callynophore only weakly developed, the inner plate of the maxilliped almost extending to the end of the outer plate, a vestigial coxa 1, a constricted inner ramus of uropod 2 and a notched telson. Morphologically, this study describes the new genus Reniuristis gen. nov. with R. brevicoxus gen. et sp. nov. as its type species.